Formation Mechanism, Growth Kinetics, and Stability Limits of Graphene Adlayers in Metal‐Catalyzed CVD Growth. Issue 14 (14th May 2018) - Wang, Zhu‐Jun; Ding, Feng; Eres, Gyula; Antonietti, Markus; Schloegl, Robert; Willinger, Marc Georg
Abstract: A new mechanism by which catalytic chemical vapor deposition of graphene spontaneously terminates at a single layer on Pt foils is discussed. This self‐limited growth regime is identified by direct imaging of adlayer graphene evolution using in‐situ environmental scanning electron microscopy. Two fundamentally different mechanisms for adlayer nucleation are revealed. Besides primary nucleation, which is the standard nucleation that occurs only at the onset of growth, a secondary nucleation of adlayers is observed near full coverage of the substrate. Direct observation reveals layer‐dependent growth kinetics and the establishment of a dynamic equilibrium between the forward reaction of carbon incorporation and the reverse reaction of graphene etching. Increasing coverage of the active catalyst gives rise to a spontaneous reversal of adlayer evolution from growth to etching. The growth reversal has important practical benefits. It creates a self‐limited growth regime in which all adlayer graphene is removed and it enables large‐scale production of 100% single‐layer graphene. Abstract : Real‐time observation of graphene growth on Pt substrates reveals mechanisms of primary and secondary adlayer formation. The growth kinetics show that a layer‐dependent dynamic equilibrium between graphene growth and hydrogen etching is established which, upon increasing coverage of the active Pt catalyst, finally results in complete removal of all adlayers. Thus, the process spontaneously terminates at the single‐layer level.